Exploration of the Archipelago's Cultural Heritage Local Wisdom and the Beauty of Traditional Arts - Dahlan, Nur Fadillah (Professorline, 2025)
This article explores the rich culture of the archipelago through an exploration of local wisdom and traditional art aesthetics. The cultural diversity of the archipelago, spanning thousands of islands with diverse communities, offers an in-depth look at the values of local wisdom reflected in traditional arts. Traditional arts in the archipelago are not only a form of artistic expression, but also an important means of maintaining and celebrating the unique cultural identity of each region. In this study, we identify some key aspects of local wisdom reflected in the Nusantara's traditional arts, including moral, spiritual, and social values that are passed down through generations. Traditional arts such as shadow puppetry, dance, carving, and textiles, not only contain symbolic meanings, but also illustrate the distinctive aesthetic beauty of each local community. Our in-depth analysis highlights the important role of traditional arts in enriching cultural identity and promoting diversity in the Nusantara society. We argue that the preservation of traditional arts is not only about maintaining cultural heritage, but also about evoking a sense of national pride and identity. Through this approach, this article seeks to broaden the understanding of the Nusantara's cultural diversity and appreciate the contribution of traditional arts in realizing unity in diversity.